Racism in Mind - Pataki, Tamas; Levine, Michael P., 1950- (Book collections on Project MUSE., 2004)
This philosophical analysis of the phenomenon of racism brings together some of the most influential analytic philosophers writing on racism today. The introduction by Tamas Pataki outlines the historical and thematic development of conceptions of race and racism, and locates the following essays against the backdrop of contemporary reactions to that development. While the framework is primarily analytic, the volume also includes essays deeply informed by psychoanalysis, phenomenology, and feminist and social theory. The fourteen chapters in this collection address three interrelated questions: What is racism? What are the causes of racism? and What are the moral and political implications of racism? Although their approaches are wide ranging, the contributors to Racism in Mind broadly endorse a psychological-characterological approach to the understanding of many aspects of racism.